1996
DOI: 10.1007/bf00408662
|View full text |Cite
|
Sign up to set email alerts
|

The effect of insulin-like growth factor-1 on adult rat cardiac contractility

Abstract: There is increasing evidence that insulin-like growth factor-1 (IGF-1) may play a role in both physiological and pathophysiological events in the mammalian myocardium. The present study investigated the acute effects of IGF-1 on isometric force development in isolated rat cardiac muscle and on intracellular calcium (Ca2+) handling in isolated cardiac myocytes. IGF-1 had a positive inotropic effect on rat ventricular papillary muscles increasing force development by 17.8 +/- 4.6%, 18.5 +/- 5.8% and 11.9 +/- 4.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
2
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(58 citation statements)
references
References 28 publications
4
51
2
1
Order By: Relevance
“…HGF is believed to be involved in regeneration of various tissues, including myocardium (13,30). IGF-I is able to prevent apoptosis and to enhance cell proliferation by activating multiple signal transduction pathways (6,11). Direct injections of plasmid DNA encoding each of the growth factors into the ischemic myocardium have been shown to increase capillary density, reduce infarct size, and improve cardiac contractile function.…”
Section: Discussionmentioning
confidence: 99%
“…HGF is believed to be involved in regeneration of various tissues, including myocardium (13,30). IGF-I is able to prevent apoptosis and to enhance cell proliferation by activating multiple signal transduction pathways (6,11). Direct injections of plasmid DNA encoding each of the growth factors into the ischemic myocardium have been shown to increase capillary density, reduce infarct size, and improve cardiac contractile function.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Myocardial hypertrophy and interstitial fibrosis, induced by high levels of IGF-1, have been reported to induce LV diastolic dysfunction in acromegalics. [37][38][39] IGF-1 has also been reported to increase inositol 1,4,5-tris-phosphate levels 40 ; to activate tyrosine kinase phosphatase, phosphatidylinositol-3-kinase, and protein kinase C [41][42][43] ; and to increase intracellular calcium level or sensitivity, [43][44][45] suggesting another mechanism for IVRT prolongation in case of IGF-1 overproduction.…”
Section: Inverse Association Of Free Igf-1 and Ivrtmentioning
confidence: 99%
“…Very briefly, GH and IGF-I receptors are expressed in cardiac myocytes (1), and IGF-I causes hypertrophy of cultured rat cardiomyocytes (2) and delays cardiomyocyte apoptosis (3). In addition, GH and IGF-I also play a direct effect on myocardial contractility, increasing the intracellular calcium content and enhancing the calcium sensitivity of myofilaments in cardiomyocytes (4,5). The existence of a relationship between GH/IGF-I and the cardiovascular system has also been suggested by clinical studies, as reported by the increased risk for cardiovascular morbidity and mortality in both GH deficiency (GHD) and excess (6 -12).…”
Section: Introductionmentioning
confidence: 99%